Pemberian jus buah vitamin C dan madu menurunkan disfungsi rongga mulut pada anak akibat kemoterapi - Hariani, Gusti Ayu Nyoman; Sulistyadewi, Ni Putu Eny; Kusumawati, I Gusti Ayu Wita (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background : Dysfunction of the oral cavity is a common side effect of chemotherapy that occurs in children who are undergoing chemotherapy. To prevent a decline in quality of life of children with cancer, immediate treatment by maintaining nutritional balance is needed. This study aimed to determine the effect of vitamin C fruit juice to dysfunction of the oral cavity in children undergoing chemotherapy at Sanglah Hospital.Methods : This was a quasi-experimental study with nonrandomized pre and posttest with control group design. Samples were taken using total sampling method, consisted of 26 children aged 3-12 years. Vitamin C intake rated by evaluation of vitamin C juice residue and dysfunction of the oral cavity were assayed by Beck Oral Assessment Scale (BOAS). The entire samples were given vitamin C fruit juice in accordance with BOAS score for 5 days. Normality test of pre-test, post-test and the difference between pre and post test data with Shapiro Wilk test showed that data were normally distributed (α> 0.05) so that data was analyzed using parametric test paired independent sample - test with a score of 0.001 and 95% level of significance. Results : Results of analysis showed differences of oral cavity dysfunction score before and after fruit juice vitamin C treatment. Before treatment, mean of oral cavity dysfunction score in control group was 13.1 ± 2.1 and 12.8 ± 0.9 in treatment group. Mean of oral cavity dysfunction score after administration of oral vitamin C fruit juice in the control group and treatment group was 10.8 ± 1.8 and 8.2 ± 1.4, respectively. Conclusion : There were an effect of vitamin C fruit juice and honey decrese of oral cavity dysfunction in children aged 3-12 years who were undergoing chemotherapy